Al-Dakhil Al-Naqliy Dengan Pemalsuan Pendapat Sahabat - Fithrotin, Fithrotin (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2020)
At the time of the Prophet Muhammad saw. the development of the interpretation of the Qur'an does not look rapidly and widely, because the priority of interpretation is still hoping for a great deal of revelation. When they found some verses that were general in nature and needed explanation, the companions immediately asked the Prophet, so that at that time there were not many verses described in detail. The Prophet's explanation of some verses serves as a guide for the companions to study the Qur'an more carefully. The spirit of the companions of the Prophet to compete in the interpretation of the Quran was very helpful to the mufassir centuries later. But some mufassirun search results against the interpretation of the companions of the Prophet sometimes received from a history that is not good, interpretation that is isra'iliyat also sometimes based on the interpretation of some friends, or some interpretation produced bya mufassir is also sometimes relied on one of the companions of the Prophet who is considered expert tafsir, The conclusion of this research is that some commentators and histories such as Husaen al-Zahabi, al-Suyuthi admitted that it would be difficult to examine the falsification of the opinions of friends, especially those who have slipped into various tafsir books, because many of the athar friends' histories have been discarded by the prophet. Sanad hadith disposal especially athar companions occurred since the time of tabi'in,more often in, the time of tabi'it tabi'in, because of the ease and the increasing number of mufassir who are vying to further expand and enrich their reference in the interpretation of interpreted verses.